Effect of Dietary Neem (Azadirachta indica) and Kadi (Murraya koenigii) Leaf Powder on Growth Performance and Nutrient Utilization in Broiler Chicken - Khulbey, Ravi; Kumar, Ashoka; Mondal, B.C.; Palod, Jyoti; Singh, P.K. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted on 180 day-old broiler chicks to evaluate the effects of neem (Azadirachta indica) and kadi (Murraya koenigii) leaf powder on the growth performance and nutrient utilization. The six dietary treatments included control (T1), basal diet supplemented with leaf powder @ 0.2% neem (T2), 0.2% kadi (T3), 0.1% kadi and 0.3% neem (T4), 0.3% kadi and 0.1% neem (T5) and 0.2% kadi and 0.2% neem (T6). Each treatment diet was fed ad lib. to three replicated groups of 10 chicks up to 42 days of age. Weekly feed intake,body weight gain, feed conversion ratio and performance index were recorded. A metabolic trial of 3 days was conducted during 6th week of feeding trial. There was a significant (P